Rebecca, not Becky : a novel - Platt, Christine A., 1976-; Greene, Catherine Wigginton (Amistad, an imprint of HarperCollinsPublishers, 2023)
Struggling to adjust to the upper-crust white suburb of Rolling Hills, Virginia, De'Andrea Whitman is challenged by her therapist to make a white girlfriend and finds one in Rebecca Myland as they are brought together to fight back against the community's rising racial sentiments.